Der aspektuale Bezugsmoment als linguistische Grundlage fuer die Beschreibung und Vermittlung des russische Verbalaspekts Ein Beitrag zu Temporalitaet und Aspektualitaet - Schlegel, Hans (Specimina philologiae Slavicae, 2000)
With the present publication on the aspeclual reference moment, the author returns to a problem that occupied the science more than three decades ago (Schlegel 1970, 1971, Scheljakin / Schlegel 1970) and has not let go since then. At that time it was a matter of a special aspect theory that would reduce the functioning of the Russian aspect to a simple principle and make the non-Slavic foreign language teacher understand it, but in the meantime it has entered into a general aspect theory - supplemented by a theory of terminativity / terminarity (T. / AT), embedded in a theory of aspectuality (Schlegel 1999 [1977]). Since the first elaborations, the field of vision has widened, the reference moment has been used (...) as a "point of reference", as a "viewing time", as a "psychic now" in the description of languages ​​other than Russian. The theory of the reference moment has a great explanatory potential for foreign language teaching in advanced learners.